Risk factors for continuous renal replacement therapy after surgical repair of type A aortic dissection - Wu, Hai-Bo; Ma, Wei-Guo; Zhao, Hong-Lei; Zheng, Jun; Li, Jian-Rong; Liu, Ou; Sun, Li-Zhong (Journal of Thoracic Disease, 2017)
Background: To identify the risk factors for continuous renal replacement therapy (CRRT) following surgical repair of type A aortic dissection (TAAD) using the total arch replacement and frozen elephant trunk (TAR + FET) technique. Methods: The study included 330 patients with TAAD repaired using TAR + FET between January 2014 and April 2015. Mean age was 47.1±10.2 years (range, 18–73 years) and 242 were male (73.3%). Univariate and multivariate analyses were used to identify the risk factors for CRRT. Results: Postoperative CRRT was required in 38 patients (mean age 50.7±10.0 years; 27 males). Operative death occurred in 12 patients (3.6%, 12/330). The mortality rate was 23.7% (9/38) in patients with CRRT and 1.0% (3/292) in those without CRRT (P